"If I know when you will arrive, I will let you walk to school:" The role of information technology. (February 2020) - Fallah Zavareh, Mohsen; Mehdizadeh, Milad; Nordfjærn, Trond
Highlights: IT interventions are still novel in the domain of promoting active school transport. Our solution gives real-time information about children's entry and exit from school. Increased parental intention to let children walk was higher among the walking pupils. For non-walking pupils more variables explained increased parental intention. Improved walking facilities potentiate the solution by the non-walking group. Abstract: Introduction: Providing a sense of supervision for parents may facilitate their children's involvement in physical outdoor activities, such as walking to school. Information technology (IT) solutions could bring more parental supervision, which in turn has the potential to enhance the proportion of walking trips to school. This study aimed to examine the role of a proposed hypothetical IT solution that gives parents real-time information about children's entrance to and exit from the school, for the intention of parents letting their children walk to school. Method: A total of 820 questionnaires were distributed among pupils aged 7–9-years across 28 elementary schools to be completed by their parents (82% return rate). Results: Compared to the group of walking pupils, increased parental intention to let their children walk to school under the proposed solution could be explained by considerably more variables in the group of pupils who did not walk to school. The findings revealed that increased parental intention was higher among the walking pupils compared to the non-walking pupils. For the non-walking pupils, enhancement of walking facilities across the school area could potentiate the use of the proposed solution by the parents, which in turn may increase the proportion of walking on school trips. In addition, boy pupils, the pupils whose parents evaluated walking more favorable, those from lower socioeconomic backgrounds, and those living in close proximity to the school could more likely benefit by shifting from non-walking to walking modes of travel, after implementation of the solution.